Unraveling and reweaving sacred canon in Africana womanhood - Ross, Rosetta E., 1955-; Amenga-Etego, Rose Mary (Lanham : Lexington Books, 2015)
In this collection, continental and diasporan African women interrogate the concept "sacred text" and analyze ways oral and written religious "texts" intersect with violence against African-descended women and girls. While the sanctioned idea of a sacred text is written literature, this project interrupts that conception by drawing attention to speech and other embodied practices that have sacral authority within the social imaginary. As a volume focused on religion and violence, essays in this collection analyze religions' authorization of violence against women and girls; contest the legitimacy of some religious "texts"; and affirm other writing, especially memoir, as redemptive. Unraveling and Reweaving Sacred Canon in Africana Womanhood arises from three years of conversation of continental and diasporan women, most recently continued in the July 6-10, 2014 Consultation of African and African Disaporan Women in Religion and Theology and privileges experiences and contexts of continental and diasporan African women and girls. Interlocutors include African traditionalists, Christian Protestants and Catholics, Muslims, and women embodying hybrid practices of these and other traditions.
Section III : Written texts -- interrogating, unmasking, and taking charge -- 'Those who entrusted their affairs to a woman will not prosper' : its implication in the Ghanaian Muslim community / Fatimatu N-Eyare Sulemanu -- Judges 19 and the virgin daughter's trauma : "small voice" implications for African Women and Girls / Elizabeth J.A. Siwo-Okundi -- Sita's story as a text of terror : a Motswana woman's impressions / Elizabeth Pulane Motswapong -- Say my name : failure to name, misnaming, and renaming as acts of violence against Africana Women / NaShieka Knight.
Includes bibliographical references and index.
Description based on print version record.
Master record variable field(s) change: 050, 650
Keywords: Women and religion -- Africa; Women and religion -- Feminist criticism; Womanist theology; Feminist theology; RELIGION / Comparative Religion; RELIGION / Essays; RELIGION / Reference; Electronic books